Kaligrafi Arab Dalam Seni Lukis Kaca Cirebon - Gozali, Amir (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2011)
Islamic culture transformation process continues to this day, the puppet is one proof of the continuity of historical reflection Indonesian culture resulting from the transformation of culture has characterized the culture of the archipelago. In addition it is also the object of puppets in the creation of works of art of Islamic calligraphy in Indonesia. Islamic Calligraphy has been media creativity of the artist to realize the creation of Islamic art that characterized the archipelago. During its development, calligraphy works, both produced by palace artist and artist from outside the palace, has managed to absorb the local cultture and accomplishment in calligraphy. In connection with this, mucullah calligraphy works in the form of works of calligraphy with the puppet motif adapted well in the archipelago, especially in Cirebon. Glass painting in Cirebon could not be separated from the cultural history of Cirebon that culture is the crystallization of several from the cultures that influence it. In the history of Cirebon culture influences from Arabic, Chinese, and Central and East Java.Acculturation in Cirebon culture integrated with peace, so that glass painting in Cirebon if observed bring a breath of uniqueness and distinctive character. Islamic Calligraphy in Cirebon is a mean of channeling creative art reflection of this artist.The trustee in Cirebon by successfully combining creative Islamic calligraphy art with elements of local art. So the calligraphy appears Cirebon identity. Traditional decorative patterns that have been developed previously distilir so as to produce beautiful calligraphic work without losing his character. Some works of calligraphy Panembahan which is stylized decorative patterns that emerge in the form of a charming figural calligraphy, monumental and filled with elements of local genius. Islamic Calligraphy presence in Indonesia has emerged as the archipelago culturesÂ  capable of moving the tradition of thinking and notices, which is capable of touching the existence, cultivate ideas, open intuition, imagination cast a meaning behind the verses as a source of expression and creativity to create works that bercitra archipelago. Keywords: Glass painting, Cirebon, Islamic Calligraphy.